2021
DOI: 10.7150/thno.58413
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immunotherapy and multi-mode therapies mediated by medical imaging of nanoprobes

Abstract: Immunotherapy is an effective tumor treatment strategy that has several advantages over conventional methods such as surgery, radiotherapy and chemotherapy. Studies show that multifunctional nanoprobes can achieve multi-mode image-guided multiple tumor treatment modes. The tumor cells killed by chemotherapies or phototherapies release antigens that trigger an immune response and augment the effects of tumor immunotherapy. Thus, combining immunotherapy and multifunctional nanoprobes can achieve early cancer dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 159 publications
(170 reference statements)
0
11
0
1
Order By: Relevance
“…The immune system appears to have both tumor-suppressive and antitumor effects, which depends on the interaction between the tumor microenvironment and the immune system. Tumor immunotherapy is mainly based on enhancing the recognition of tumor antigens by antigen-presenting cells (APCs) and T lymphocytes, enhancing the immune response, relieving the inhibitory effect of immune cells, and promoting the antitumor immune response [17]. ICIs (immune checkpoint inhibitors) are committed to relieving the inhibitory effect of tumors on T lymphocytes, thereby enhancing the activation, prolifer-ation, and differentiation of T lymphocytes and enhancing immune function, increasing the abundance of proteins involved in the immune response.…”
Section: Icis Monotherapymentioning
confidence: 99%
“…The immune system appears to have both tumor-suppressive and antitumor effects, which depends on the interaction between the tumor microenvironment and the immune system. Tumor immunotherapy is mainly based on enhancing the recognition of tumor antigens by antigen-presenting cells (APCs) and T lymphocytes, enhancing the immune response, relieving the inhibitory effect of immune cells, and promoting the antitumor immune response [17]. ICIs (immune checkpoint inhibitors) are committed to relieving the inhibitory effect of tumors on T lymphocytes, thereby enhancing the activation, prolifer-ation, and differentiation of T lymphocytes and enhancing immune function, increasing the abundance of proteins involved in the immune response.…”
Section: Icis Monotherapymentioning
confidence: 99%
“…Our study showed that the tumor-relative markers were altered to a normal stage in vitro and in vivo, which ultimately induced apoptosis of OLK cells and hindered malignant transformation progression. Huge amounts of research prove that the PTT-induced cells damage can release the damage-associated molecular patterns (DAMP) [ 62 ], which can initiate the immune response in tumor therapy. Though immunotherapy in OLK is rare, its development is viable and promising, bringing new sights and possibilities in OPMDs treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Engineering therapeutics with multispecificity to target different pathways is one promising strategy consisting of two major categories, non-obligate and obligate multispecific [39,40]. Non-obligate multispecific therapeutics are recombinant antibody-based molecules that simultaneously modulate two or more signaling pathways when binding their targets and are similarly efficacious to a mixture of distinct antibodies.…”
Section: Multivalency and Multispecificitymentioning
confidence: 99%